Environmental education and political pedagogical project in courses in the Universidade Federal do Ceará - Oliveira, Ivan de; Fernandes, Rafael Gomes; Menezes, Maria Ozilea Bezerra de; Maia, Luis Parente (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2015)
Thestudy aimed toverify the presence ofenvironmental componentsinPolitical Pedagogical Projects(PPPs) of undergraduateof the FederalUniversity of Ceará-UFC, taking assamplethe courseslinked to theTechnology Center. It isessentially abibliographical anddocumentary research. Besides theliterature on thesubject studied, disciplinary menuswere analyzed. Thenit is necessaryreorganization ofPPP's courseswiththe aim of introducingthe set ofenvironmental principles andcomponentsdefendantsthe National CurricularGuidelines for EnvironmentalEducation